The influence of Entrepreneurial Capital on the performance of subcontracting SMMEs in Gauteng, South Africa - Rampa, Mmatsatsi (University of the Witwatersrand, Johannesburg, 2019)
This study explores the prospect of entrepreneurial capital in stimulating SMME performance. It seeks to investigate the use of non-financial capital (entrepreneurial capital) in SMMEs registered under the CIDB, in the general building sector, and its influence on SMME performance. It unpacks the two dimensions of entrepreneurial capital which are entrepreneurial commitment and entrepreneurial competence. This study is a quantitative research, based on a positivism research paradigm. The survey structured research instrument was collected using Qualtrics. The primary data, with a sample size of 377, was distributed using emails and was consolidated via Qualtrics. The data analysis and interpretation was based on descriptive analysis, correlation analysis, exploratory analysis and multiple linear regression analysis. The study was initially designed to analyse the two dimensions (entrepreneurial competence and commitment) collectively with their antecedents (opportunity, relationship, conceptual, organising and strategic competencies); and (normative, continuous and affective commitment) respectively. The survey findings could not converge into a clear multi-dimensional factor structure for each construct. Hence the analysis could only be undertaken at the dimensions level without breaking them down any further into their sub-sets. Entrepreneurial competence was the only one of the two that emerged as the statistically significant predictor of SMME performance. However, both dimensions had a positive influence with business performance, though entrepreneurial commitments’ influence was weak and not statistically significant. SMME owners/managers should continuously advance and assess their specific entrepreneurial competence in order to positively influence their business performance. Policy makers, training and support programmes should align content to specific entrepreneurial competence.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2019.
Keywords: Entrepreneurial commitment; Entrepreneurial competence; Business performance; CIDB; General building; UCTD; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure